The Use of Artificial Intelligence Tools in the Processes of Motivating Employees in the Organization - Bozena E. MATUSIAK (Communications of International Proceedings, 2024)
The paper deals with the development of artificial intelligence and the application of AI tools in HRM. As a result of a preliminary analysis of the literature, a research gap was identified regarding the study of support of the motivation function through the use of AI tools. In the next step, a research project on employee acceptance of the use of AI tools in the HR motivation processes using the example of AI Agents was planned and prepared.
Keywords: Artificial Intelligence; Human Resource Management; Motivation and Evaluation Processes; AI Agents